2006
DOI: 10.1111/j.1460-9568.2005.04562.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes of CaMKII localization, activity and function during postembryonic CNS remodelling in Manduca sexta

Abstract: Insect metamorphosis is a compelling example of postembryonic remodelling of neuronal structure and synaptic connectivity as larval and adult behaviours place distinct demands on the CNS. Holometabolous insects such as the moth Manduca sexta have long served as suitable models for the study of steroid effects on CNS remodelling, but activity and calcium-dependent mechanisms have been found to act in concert with hormonal signals. This study examines developmental changes in the localization and the activationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 77 publications
(124 reference statements)
0
24
0
2
Order By: Relevance
“…Investigations in M. sexta revealed an increase in postsynaptic CaMKII activation during early pupal stages (Burkert and Duch, 2006). This was shown to be correlated with dendritic filopodia collapse and rapid synaptogenesis, indicating a possible functional role of CaMKII in postembryonic development of neuronal (dendritic) circuitry.…”
Section: General Distribution Of Pcamkii In the Honeybee Brainmentioning
confidence: 95%
See 1 more Smart Citation
“…Investigations in M. sexta revealed an increase in postsynaptic CaMKII activation during early pupal stages (Burkert and Duch, 2006). This was shown to be correlated with dendritic filopodia collapse and rapid synaptogenesis, indicating a possible functional role of CaMKII in postembryonic development of neuronal (dendritic) circuitry.…”
Section: General Distribution Of Pcamkii In the Honeybee Brainmentioning
confidence: 95%
“…Several studies have also suggested a role of CaMKII in neuronal plasticity in insects. For example, in the moth Manduca sexta, CaMKII is likely involved in large-scale dendritic remodeling during postembryonic development (Burkert and Duch, 2006). In the honeybee Ca 2þ was…”
mentioning
confidence: 99%
“…However, we do not favor the latter explanation based on previous work on giant neurons in culture (Yao and Wu, 2001) that respond to CaMKII antagonists, and our own results with the constitutively active CaMKII-T287D suggest that these neurons and relevant synapses of the GFS contain the molecular machinery to respond to the elevated kinase activity. This, along with the abundant neuronal expression of the kinase, suggest that it is normally present in the circuit, although its unequivocal demonstration (Schmitt et al, 2004;Burkert and Duch, 2006) is not trivial and is the subject of ongoing work. Our data indicate that the electrophysiological phenotypes result from sustained CaMKII activity during development of cholinergic synapses.…”
Section: Discussionmentioning
confidence: 99%
“…The in-vivo treatment of animals with the CaM kinase blocker KN-93 followed the protocol described by Burkert and Duch (2006). The blocker was dissolved in deionized water (5 mM), and 40 μl of this solution was injected into the animal as described by Lohr et al (2005), resulting in a final concentration of KN-93 in the hemolymph of approximately 100 μM.…”
Section: Animals and Preparationmentioning
confidence: 99%
“…CaM kinase II is involved in the maturation and stabilization of dendrites and synapses in the frog optic tectum (Zou and Cline 1996;Wu and Cline 1998). Recently, Burkert and Duch (2006) have described the CaM kinase II dependence of MN5 motoneuron reorganization during metamorphosis of the sphinx moth Manduca sexta. In developing antennal lobe neurons of Manduca, we have found a changing pattern of acetylcholine receptortriggered Ca 2+ oscillations during synaptogenesis (Lohr 2003).…”
Section: Introductionmentioning
confidence: 98%